2014
DOI: 10.3126/kumj.v11i1.11053
|View full text |Cite
|
Sign up to set email alerts
|

A case of Synchronous Malignancy of Stomach and Kidney

Abstract: The synchronous occurrence of primary renal cell carcinoma with gastric cancer is very rare. We report a case of 41 year old male who presented on 05/07/2011 to M S Ramaiah hospital, Bangalore with history of fever, pain abdomen and malena. Ultrasound abdomen and pelvis showed large heterogenous mass arising from the upper pole of left kidney. Computed tomography of the abdomen showed left renal cell carcinoma. Renal biopsy showed features consistent with renal cell carcinoma -clear cell type. Oesophagogastrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…The most commonly reported risk factor was smoking [2,4,17,18,20,[22][23][24][25]. The most frequent clinical presentations were upper or lower gastrointestinal (GI) bleeding, nonspecific Multiple combinations of surgical treatments are described, including partial gastrectomy/radical nephrectomy [5], subtotal gastrectomy/partial nephrectomy [6,19], total gastrectomy/radical nephrectomy [17,20], endoscopic gastric resection/radical nephrectomy [24], partial gastrectomy/total nephrectomy [17], mucosectomy/renal active surveillance [18], and total gastrectomy/renal active surveillance [22]. Among the surgical approaches for gastric cancer, partial gastrectomy was predominant, followed by total gastrectomy and subtotal gastrectomy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly reported risk factor was smoking [2,4,17,18,20,[22][23][24][25]. The most frequent clinical presentations were upper or lower gastrointestinal (GI) bleeding, nonspecific Multiple combinations of surgical treatments are described, including partial gastrectomy/radical nephrectomy [5], subtotal gastrectomy/partial nephrectomy [6,19], total gastrectomy/radical nephrectomy [17,20], endoscopic gastric resection/radical nephrectomy [24], partial gastrectomy/total nephrectomy [17], mucosectomy/renal active surveillance [18], and total gastrectomy/renal active surveillance [22]. Among the surgical approaches for gastric cancer, partial gastrectomy was predominant, followed by total gastrectomy and subtotal gastrectomy.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the management of patients with renal carcinoma, multiple reviews revealed that radical nephrectomy was the most frequently performed surgical intervention, followed by total nephrectomy, partial nephrectomy, and two cases treated with active surveillance. Diagnostic renal carcinoma was more frequently on the left side with nephrectomy (partial, total, or radical) [5,6,19,[22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Literature search shows only 3 cases reported from India. [13][14][15] Occurrence of multiple primary malignancies can be due to various genetic events or common environmental risk factors such as smoking, alcoholism, family history of cancer or immunological defects and prior irradiation or chemotherapy. 16 Various familial cancer syndromes are linked to SPM including lynch I and II syndromes, Li-Fraumeni syndrome, Fanconi anaemia, xeroderma pigmentosum and Von Hippel-Lindau.…”
Section: Discussionmentioning
confidence: 99%
“…2 Though the combination of gastro-intestinal and genitourinary tumours are not very uncommon, synchronous gastric and renal malignancies are very rare (0.11-0.37%) and only 3 cases have been reported from India. 3,[13][14][15]…”
Section: Introductionmentioning
confidence: 99%